Математична модель режимів роботи системи асинхронних двигунів димотягів теплових електричних станцій - Василів, К.М. (Електротехніка і електромеханіка, 2017)
Розроблено математичну модель електротехнічного комплексу: «Електрична мережа – трансформатор – два асинхронні двигуни» у фазних координатах, орієнтовану на явні методи числового інтегрування системи диференціальних рівнянь. На базі математичної моделі створено програмний комплекс і проведено дослідження електромагнітних і електромеханічних процесів та встановлено основні закономірності їх перебігу в режимах пуску, зупинки та самозапуску асинхронних двигунів димотягів енергоблоку теплової електричної станції. Разработана математическая модель электротехнического комплекса: «Электрическая сеть – трансформатор – два асинхронных двигателя» в фазных координатах, ориентированная на явные методы численного интегрирования системы дифференциальных уравнений. На базе математической модели создан программный комплекс и произведено исследование электромагнитных и электромеханических процессов и установлено основные закономерности их протекания в режимах пуска, останова и самозапуска асинхронных двигателей дымососов энергоблока тепловой электрической станции. Purpose. Development of a model-software complex (MSC) for computer analysis of modes of the system of induction motors (IM) of smoke exhausters of thermal power plant (TPP), the basic elements of which are mathematical models and corresponding software written in the programming language FORTRAN. Methodology. Mathematical model serves as a system of differential equations of electrical and mechanical condition. The equation of electric state is written in phase coordinates based on Kirchhoff's laws, and mechanical condition described by the d'Alembert equation. Mathematical model focuses on explicit numerical integration methods. Scientific novelty. The equation of state of electrical connections takes into account the mutual electromagnetic circuits for transformer of own needs (TON) and induction motors and interdependence (in all possible combinations) between: TON (from which motors powered) and each of the two IM and blood pressure between themselves. The complex allows to simulate electromagnetic and electromechanical processes in transitional and steady, symmetric and asymmetric modes including modes of self-induction motors. Results. Complex is used for computer analysis of electromagnetic and electromechanical processes and established the basic laws of motion modes of starting, stopping and self-start of IM of smoke exhausters of the TPP unit. Practical value. The complex is suitable for computer analysis of modes of other similar units of own needs of thermal power plants.